2019
DOI: 10.3390/molecules24213938
|View full text |Cite
|
Sign up to set email alerts
|

Reaction of Papaverine with Baran DiversinatesTM

Abstract: The reaction of papaverine with a series of Baran DiversinatesTM is reported. Although the yields were low, it was possible to synthesize a small biodiscovery library using this plant alkaloid as a scaffold for late-stage C–H functionalization. Ten papaverine analogues (2–11), including seven new compounds, were synthesized. An unexpected radical-induced exchange reaction is reported where the dimethoxybenzyl group of papaverine was replaced by an alkyl group. This side reaction enabled the synthesis of additi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 41 publications
(64 reference statements)
0
6
0
Order By: Relevance
“…After the FDA’s approval of auranofin (tetra- O -acetylglucose-1-thiolgold(I) triethylphosphine complex) as a therapy for rheumatoid arthritis, the gold-based drugs have attracted special attentioin. The exploitation of gold complexes has led to vast diversity of gold compounds of biological relevance, including anti-cancer, anti-inflammatory and antiparasitic agents [ 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 ].…”
Section: Introductionmentioning
confidence: 99%
“…After the FDA’s approval of auranofin (tetra- O -acetylglucose-1-thiolgold(I) triethylphosphine complex) as a therapy for rheumatoid arthritis, the gold-based drugs have attracted special attentioin. The exploitation of gold complexes has led to vast diversity of gold compounds of biological relevance, including anti-cancer, anti-inflammatory and antiparasitic agents [ 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 ].…”
Section: Introductionmentioning
confidence: 99%
“…To further expand our library and thus explore SARs within the halogenated series, we sought to engage Baran’s innovative Diversinate™ chemistry for the late-stage trifluoromethylation of N -Boc protected thiaplakortone A [ 26 , 27 ]. Consequently, a mixture of compound 2 and zinc trifluoromethanesulfinate in CH 2 Cl 2 /H 2 O was stirred for 1 h at 4 °C (see Scheme 2 ).…”
Section: Resultsmentioning
confidence: 99%
“…In addition, the fungal aromatic peroxygenase (AaP) was reported to catalyze the N-oxygenation of pyridine and related compounds (Ullrich et al, 2008). Nitrogen-rich heterocyclic compounds are used to treat various human diseases, and these motifs are found in many isoquinoline alkaloid drugs (Egbewande et al, 2019) IUCrJ (2021). 8, 684-694 Figure 2 HPLC chromatogram and LC-MS spectra (inside the box) for (a) papaverine and (b) tetrahydropalmatine.…”
Section: Functional Characterization Of Cyp105d18mentioning
confidence: 99%
“…However, modified papaverine may have better efficacy and reduced cytotoxicity and can easily be metabolized by the body. Chemical modification of papaverine for C-H functionalization, N-oxidation (Egbewande et al, 2019) and Odemethylation has been reported (Brossi & Teitel, 1970). These classical approaches are time-consuming and costly and may suffer from poor regio-selectivity compared with enzymecatalyzed reactions.…”
Section: Introductionmentioning
confidence: 99%